Analytical reasoning with external representations supporting the stages of selection, construction and use - Cox, Richard; Brna, Paul (1994)
Abstract: "External representations (ERs) are effective in reasoning due to both their cognitive effects and semantic properties. Educational hypermedia systems frequently use graphically-based approaches to structure information and several intelligent educational systems have employed graphics or graphical interfaces. However, no system to date, of which we are aware, has attempted to offer learner support in the construction, selection and use of a range of representations during reasoning. Those stages are the central concerns of this paper. We argue that they are important for analytical problem solving and a mechanism is proposed whereby learners may resolve impasses in reasoning via switching ER modalities. Literature on ER use in a wide range of domains is reviewed and a distinction is made between studies in which subjects self-construct ERs and those in which they use prefabricated ERs. We describe an environment (switchER) for solving analytical reasoniong problems. SwitchER has been used to explore hypotheses relating to processes of: representation selection, construction, and use in problem solving, and the effects of prior knowledge. Problem characteristics (e.g. complexity, level of determinancy) are also shown to be important. The results indicate the importance of the issues and inform the design of an intelligent system switchER II -- an interactive learning environment that facilitates learning via ER switching."
Keywords: Bionics and artificial intelligence; Education and training; Psychology; Künstliche Intelligenz; Artificial intelligence